Role and Contribution of Political Parties in the Political Movement of 2006 - Bahadur Bhandari, Arjun; Yuliastina, Roos (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2024)
Abstract The 2006 Nepalese political movement marked a significant shift in the country's democratic history, with political parties playing a crucial role in garnering support and influencing public expectations. The democratic revolution in 2006 brought multiparty democracy back to Nepal, and this article explores the tactics, difficulties, and success of political parties in launching and maintaining the movement. Using historical narratives, primary materials, and academic examinations, the study explores how political parties evolved into catalysts for transformation, galvanized the populace, and engaged in negotiations with the king to initiate a new phase of democracy in Nepal. The movement's success was driven by complex dynamics influenced by social, political, and economic elements. The study uses historical research and political mobilization theories to investigate the role and contribution of political parties in the 2006 movement, examining their role as change agents, tactics, and influence on democratic transitions. The results provide insights into how political parties affect democratic processes, highlighting their role as uniting factors within movements. Keywords: Political parties, authoritarianism, totalitarian states, violent conflict, and democratic movement. Abstrak Gerakan politik Nepal tahun 2006 menandai pergeseran yang signifikan dalam sejarah demokrasi negara ini, dengan partai-partai politik memainkan peran penting dalam menggalang dukungan dan mempengaruhi ekspektasi publik. Revolusi demokrasi pada tahun 2006 membawa demokrasi multipartai kembali ke Nepal, dan artikel ini mengeksplorasi taktik, kesulitan, dan keberhasilan partai-partai politik dalam meluncurkan dan mempertahankan gerakan tersebut. Dengan menggunakan narasi sejarah, materi primer, dan kajian akademis, penelitian ini mengeksplorasi bagaimana partai-partai politik berevolusi menjadi katalisator transformasi, menggembleng rakyat, dan terlibat dalam negosiasi dengan raja untuk memulai fase baru demokrasi di Nepal. Keberhasilan gerakan ini didorong oleh dinamika yang kompleks yang dipengaruhi oleh elemen-elemen sosial, politik, dan ekonomi. Penelitian ini menggunakan penelitian sejarah dan teori mobilisasi politik untuk menyelidiki peran dan kontribusi partai politik dalam gerakan 2006, mengkaji peran mereka sebagai agen perubahan, taktik, dan pengaruhnya terhadap transisi demokrasi. Hasilnya memberikan wawasan tentang bagaimana partai politik mempengaruhi proses demokrasi, dengan menyoroti peran mereka sebagai faktor pemersatu dalam gerakan. Kata Kunci: Partai politik, otoritarianisme, negara totaliter, konflik kekerasan, dan gerakan demokrasi